ToGo Cabs: an Android phone cab reservation application - Meesala, Nirupama Mrinalini (Kansas State University, 2012)
Now a days, people are more inclined towards owning a smart phone. In such a scenario, mobile application development is one of most sought after platforms. Android is one of the largest platforms that run in most smart phones from manufacturers like Samsung, HTC etc. ToGo Cabs is an Android phone cab reservation application which targets the residents of the state of Kansas. While some cab services boast about their cab being just a call away, some other taxi services boast about the punctuality of their service. Unfortunately, at the end of the day, the passengers are just tired of waiting at different locations for the cab that they have just reserved to pick them up and take them home. What we need is a reliable mobile application which reserves a cab for us from a specific place at a certain time and which tells its users the status of the cab in order to keep them from waiting for long hours. ToGo Cabs serves just that purpose. ToGo Cabs allows the users to get a cab from any location in the state of Kansas, even if they seem to be lost. One does not have to spend hours on phone with the cab services to tell them where exactly you are located currently. The Global Positioning System takes care of the current location for the users. This application shows the route to the user, which the cab would take to reach to the destination. Once a user reserves a cab, he is acknowledged with a confirmation number which he can further use to check the cab status. The application provides the user the facility to e-mail or text his confirmation number. The application can also set a reminder notification just 15 minutes before the cab pick-up. The user can also check all the trips that he has made so far, from the application.
Keywords: Android; Cab; Mobile; Samsung; Taxi; Computer Science (0984)